2012
DOI: 10.1097/aog.0b013e31823d3aea
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Pulmonary Response After Fetoscopic Tracheal Occlusion for Severe Isolated Congenital Diaphragmatic Hernia

Abstract: Fetal endoscopic tracheal occlusion improves survival rate by increasing the lung size and pulmonary vascularity in fetuses with severe congenital diaphragmatic hernia. The pulmonary response after fetal endoscopic tracheal occlusion can be used to predict neonatal survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 39 publications
(30 reference statements)
2
35
0
1
Order By: Relevance
“…Cannie et al [13] showed a significant association between lung response at about 3 weeks from FETO, measured as the increase in total lung volume by MRI, and postnatal survival. Similarly, Ruano et al [14] reported that the total lung volume measured by three-dimensional ultrasound and the contralateral pulmonary vascularization index at 4 weeks from FETO were independently associated with survival. Future large studies combining fetal ultrasound and MRI measurements could be useful to provide accurate preoperative prediction of lung response to tracheal occlusion, and therefore to define the subgroup of fetuses with CDH that would benefit most from FETO.…”
Section: Discussionmentioning
confidence: 99%
“…Cannie et al [13] showed a significant association between lung response at about 3 weeks from FETO, measured as the increase in total lung volume by MRI, and postnatal survival. Similarly, Ruano et al [14] reported that the total lung volume measured by three-dimensional ultrasound and the contralateral pulmonary vascularization index at 4 weeks from FETO were independently associated with survival. Future large studies combining fetal ultrasound and MRI measurements could be useful to provide accurate preoperative prediction of lung response to tracheal occlusion, and therefore to define the subgroup of fetuses with CDH that would benefit most from FETO.…”
Section: Discussionmentioning
confidence: 99%
“…Severe forms of isolated CDH are associated with high neonatal mortality and morbidity due to extremely reduced lung volumes, liver herniation and decreased pulmonary vascularization. Fetal endoscopic tracheal occlusion performed between 26 and 30 weeks (standard FETO) has been shown to increase fetal pulmonary size and vascularity, and to improve neonatal survival in isolated cases of severe CDH. Fetal pulmonary response following FETO can be used to predict outcome and is dependent on size of the fetal lung prior to the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Congenital diaphragmatic hernia affects approximately 1 in 3000 live births and is associated with high rates of mortality, especially in cases with pulmonary hypoplasia and pulmonary arterial hypertension . Fetoscopic tracheal occlusion has been suggested for severe forms of CDH …”
mentioning
confidence: 99%